Kepemimpinan Kiai dalam Pengembangan Pondok Pesantren al Urwatul Wutsqo Jombang: (Studi Kasus di MTs Salafiyah Syafi'iyah Tebuireng) - Sunardi Sunardi (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2017)
Pesantren as the oldest of educational institutions has fulfilled in preparing religion expert an scholars, besides, it also created many freedom fighter and national leaders. The leadership in pesantren of Al Urwatul Wutsqo has two types, namely charismatic and democratic. The charismatic leader can be seen from his owned science, firmness, wisdom, good, obedient, sincere, and fair in organizing and managing his pesantren. He is also altruistic than himself. Therefore, many people are disinclined him. Meanwhile his democratic can be viewed from his action or policy always includes his subordinates. The results have been achieved are: 1) organization of educational institutions, both formal and non formal, 2) education based on the Qur'an, the curriculum of education is oriented to implement al Qur'an and hadith verses. Besides, the pupils must teach and spread them, 3) carrying out free education from cottage to college, 4) developing the pupils talents in a variety of skills for example agriculture, livestock, buildings, the furniture, sewing, and many others.